Philosophy as Way of Life for Christians ? Iamblichan and Porphyrian Reflections on Religion, Virtue, and Philosophy in Thomas Aquinas - Hankey, Wayne (Laval théologique et philosophique, 2003)
AbstractPierre Hadot’s purpose in developing the notion of ancient philosophy as exercice spirituel was to provide an alternative to religion. Within this framework Hadot blames the triumph of Christianity and medieval scholasticism as exemplified in Aquinas for the perte de la philosophie comme manière de vivre. The judgment he applies to Aquinas falls equally on ancient Neoplatonism. In fact, however ; for both, there is nothing abstract about the theory philosophy gives to the ascent to God : philosophy is a way of life which transforms us towards deiformity. Like its Neoplatonic predecessor, the mediaeval university contained philosophy as exercice spirituel within a Christian spirituality which also directed intellectuals towards a supernatural felicity.